Effect of aging on the spectral and solar reflectance of high-albedo roofing materials : experimental investigation - Lim, Qiu Ling. (2012)
High-albedo roofing materials are mainly used for obtaining a reduction in a building’s energy consumption and it has been used by buildings around the world for that purpose. The roofs are coated with a finish that possesses high reflectivity which reduces the surface temperatures and in turn lowers the amount of heat being transferred into a building. However, even if the roofing material is able to produce the highest reflectance readings, the trend must be able to last. The durability of the coatings have to be known so that it can be replaced or recoated once its solar reflectance is not as strong as before. Earlier research has shown that weathering does have effect on the roofing materials. Thus, the objective of this experiment is to investigate the effects of aging on high-albedo materials. This report will cover how the chemical composition and its percentage present in each type of paint will affect the solar reflectance. It will also include rainfall data which is a factor that affects the solar reflectance. The effect on the solar reflectance will be compared using the type of base material used, the surface roughness and the angle of the slope rack. The decrease in solar reflectance is attributed mainly to the slope of the racks. This key factor will in turn determine how the rainfall and aging affect the samples. The higher the amount of rainfall will enhance weathering to the material on 0° slope due to their characteristic of trapping the water. Next, emittance measurements are carried out and it is influenced by the rainfall frequency. A new procedure is implemented to find out whether dust accumulation will affect the solar reflectance over time. Recommendations are included as suggestions to develop the experimental investigation on the effect of aging on the solar reflectance of high-albedo roof materials.